A proposed development of the Brokenshirian values scale - Encabo, Henry C. (Animo Repository, 2001)
The proposed study is designed to develop a scale that will assess particular values of students uniquely and purportedly nurtured by Brokenshire College (BC). It is intended to produce a standard scale that may be used for various assessment purposes which may cover the classroom setting or whole institution itself.This instrument development project will undergo four phases of scale construction. For the content domain search phase, about 7 department heads together with the college president and vice-president for academic affairs will sit as participants for identifying and defining value constructs embedded in the BC mission and vision statement, as well as identify indicators of such values. In addition, 10 selected teachers will also be tapped as judges in classifying behavioral indicators of certain values, as a form content validation. In the pre-tryout, when items will be checked for ambiguity and other characteristics, about 50 randomly selected non-BC college and high school students will be asked to answer and comment on the scale items. In the tryout scale, 200 randomly selected college and high school students will be invited as respondents to answer the scale. Selection will be voluntary across all levels. In the criterion validation process, about 100 randomly selected college and high school students and their parents will be tapped as participants. In the standardization and norming phase, about 300 randomly selected college and high school students will be tapped. In order to develop the Brokenshirian Values Scale, the Mission-Vision Statement Values Questionnaire and the Behavior Criterion Questionnaire will be developed and constructed by the researcher in aid of data gathering.For the content domain search phase data will be analyzed in both qualitative and quantitative methods. The values identified will be presented in a frequency and distribution form and ranked. Item analysis will proceed using corrected-item total corrections and coefficient alpha as measures of inter-item consistent.